ChemInform Abstract: Electron‐Deficient Alloxazinium Salts: Efficient Organocatalysts of Mild and Chemoselective Sulfoxidations with Hydrogen Peroxide. Issue 18 (6th May 2014) - Menova, Petra; Dvorakova, Hana; Eigner, Vaclav; Ludvik, Jiri; Cibulka, Radek
Abstract A series of substituted alloxazinium perchlorates are prepared and tested as catalysts for the oxidation of sulfides to sulfoxides with hydrogen peroxide.